Effectiveness of Continuous Nursing Care on Quality of Life and Management of Complications in Patients with Ostomy Surgery: A Systematic Review - I Made Dwi Budhiasa Ari Serengga; Luh Gede Wirani Riskayanti Darmawan; Lisa Isdaryanti; Dwi Puji Lestari; Kiki Fajar Nurhidayah; Abu Bakar (Indonesian Journal of Global Health Research, 2025)
Individuals undergoing ostomy surgery frequently encounter various physical, emotional, and social challenges that may adversely affect their quality of life. Continuous Nursing Care (CNC) has been recognized for its potential in strengthening self-care skills and decreasing the incidence of postoperative complications. This review seeks to evaluate the influence of CNC on enhancing life quality and addressing complications among individuals with an ostomy. Objective to determine the effectiveness of Continuous Nursing Care (CNC) in improving quality of life and managing complications among patients undergoing ostomy surgery. This systematic review was conducted in accordance with the PRISMA 2020 guidelines. A comprehensive literature search was performed for studies published between 2019 and 2023, utilizing Boolean operators and MeSH terms: ("nursing" OR "nurse" OR "care") AND ("ostomy" OR "stoma") AND ("continuous") AND ("management") AND ("quality of life") AND "complication", across five electronic databases: Scopus, PubMed, Web of Science, ScienceDirect, and ProQuest. The initial search yielded 968 articles. After removing 28 duplicates, 940 articles remained for title and abstract screening. A total of 151 full-text articles were assessed for eligibility, and 13 studies met the inclusion criteria for the final synthesis. The included studies comprised randomized controlled trials (RCTs) and quasi-experimental designs evaluating Continuous Nursing Care (CNC) interventions among ostomy patients, with outcome measures including quality of life, self-care ability, psychological well-being, and complication management. Methodological quality was appraised using the Joanna Briggs Institute (JBI) critical appraisal tools for both RCTs and quasi-experimental studies. Only studies scoring above 65% were included in the final analysis. Thirteen studies fulfilled the inclusion criteria. CNC interventions including structured education, telehealth services, home-based care, and psychosocial support were shown to enhance quality of life, improve self-care abilities, and reduce complications after surgery. Furthermore, CNC demonstrated effectiveness in decreasing peristomal infections, psychological distress (e.g., anxiety and depression), and in promoting self-efficacy and emotional adjustment in ostomy patients. Continuous Nursing Care (CNC) has been identified as a promising strategy to enhance quality of life, psychological health, and self-care capacity, while also reducing the risk of complications in individuals with an ostomy. Nonetheless, the variability in intervention models highlights the necessity for additional research utilizing theory-based frameworks, larger sample sizes, and meta-analytic methods to determine the most effective care approaches.